Power electronics education using Mathcad - Kennedy, Robert T.; Ismail, Daut (Universiti Teknologi Malaysia (UTM), 2008)
Organized by Universiti Teknologi Malaysia (UTM), 12th - 13th December 2005 at Johor, Malaysia.